Comprehensive and High‐throughput Electrolysis of Water and Urea by 3–5 nm Nickel and Copper Coordination Polymers. Issue 21 (8th September 2021) - Kumar, Ashwani; Parvin, Sahanaz; Das, Raj Kumar; Bhattacharyya, Sayan
Abstract: Metal‐organic coordination polymers (CP) have attracted the scientific attention for electrochemical water oxidation as it has the similar coordination structure like natural photosynthetic coordinated complex. However, the harsh synthesis conditions and bulky nature pose a major challenge in the field of catalysis. Herein, 3–5 nm CP particles synthesized at room temperature using aqueous solutions of Ni 2+ /Cu 2+ and 2, 5‐dihydroxyterepthalic acid as precursor were applied for alkaline water and urea electrolysis. The overpotential required is only 300 mV at 10 mA cm −2 by Nano‐Ni CP for water oxidation, with turnover frequency (TOF) of 21.4 s −1 which is around 8 times higher than its bulk‐counterpart. Overall water and urea splitting were achieved with Nano‐Cu (−) ∥ Nano‐Ni (+) couple on Ni foam at 1.69 and 1.52 V to achieve 10 mA cm −2, respectively. High electrochemical surface area (ECSA), high TOF, and enhanced mass diffusion are found to be the key parameters responsible for the state‐of‐the‐art water and urea splitting performances of nano‐CPs as compared to their bulk counterparts. Abstract : Room temperature processed nanosized Ni and Cu CP catalyze electrochemical water and urea splitting. With Nano‐Ni anode and Nano‐Cu cathode on Ni foam in alkaline medium, overall water and urea splitting are performed requiring cell voltages of 1.69 and 1.52 V to achieve 10 mA cm −2, respectively.